2014
DOI: 10.1055/s-0033-1360478
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Removal for Mediastinal Nodal Stations for Patients with Clinical Stage I Non-Small Cell Lung Cancer: Effect on Outcome

Abstract: The extent of dissection of mediastinal lymph nodes affected the clinical outcomes of our study patients with clinical stage I NSCLC. At least evaluation of lobe-specific lymph node dissection is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…It is considered a standard surgical treatment for patients diagnosed preoperatively with lymph node metastases. However, complete lymph node dissection is not regarded as a routine surgical procedure for patients intraoperatively diagnosed as stage I NSCLC, as some studies have demonstrated a lack of significant differences in outcome between selective lymph node sampling and complete lymph node dissection in patients with early-stage lung cancer [13, 17]. …”
Section: Discussionmentioning
confidence: 99%
“…It is considered a standard surgical treatment for patients diagnosed preoperatively with lymph node metastases. However, complete lymph node dissection is not regarded as a routine surgical procedure for patients intraoperatively diagnosed as stage I NSCLC, as some studies have demonstrated a lack of significant differences in outcome between selective lymph node sampling and complete lymph node dissection in patients with early-stage lung cancer [13, 17]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the number of resected N1, N2, or total LN station was not associated with survival. This is contrary to recent studies that have indicated that the number of LNs has no significant effect on OS and that have recommended that a complete systematic pulmonary and mediastinal lymphadenectomy should be performed in NSCLC 29,30. This may be because in some LN stations, examining minor LNs alone cannot meet the standard of accurate staging.…”
Section: Discussionmentioning
confidence: 59%
“…There were three studies by the same research group based on overlapping patients; therefore, only the study with the most complete data was included . Finally, 13 retrospective cohort studies but no RCTs were included, with a total of 4343 patients (730 patients with DM and 3613 patients without) . The main data extracted from these included studies is listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Some studies found that DM was significantly correlated with worse OS and RFS in patients with surgically treated NSCLC, [8][9][10] while others found no significant difference. [11][12][13] However, it should be noted that almost all previous studies included a very limited sample of patients with DM, [8][9][10][11][12][13][15][16][17][25][26][27][28] with only one study including a sample of over 100 DM patients. 26 A previous meta-analysis with a sample of 146 DM patients found that patients with DM tended to have a poor prognosis compared to those without, with marginal statistical significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation